Improved Dynamic Response of a Single-Phase-Integrated KY Boost Converter with an MLI System of a DC-AC Converter in Motor Speed Regulation - V. Mohan; K. Nandakumar (International Transactions on Electrical Energy Systems)
KY boost converter (KBC) finds wide application in photovoltaic (PV) and single-phase inverters. In this study, a novel KBC containing seven levels of a multilevel inverter (MLI) is presented. Here, KBC between the direct current (DC) source and the inverter is proposed. Moreover, the authors considered a closed-loop response of the KBC-MLI system with a proportional integral (PI) controller and a fractional-order PID (FOPID) Controller. The main purpose of this suggested technique is to match the output current, total harmonic distortion (THD), and dynamic response of closed-loop PI and FOPID-controlled KBC-MLI systems. The proposed model is simulated with the MATLAB software, and the attained outcome illustrated an enhanced dynamic performance by using the FOPID-controlled KBC-MLI system. The simulation results of the KBC-MLI technique have been evaluated against the theoretical models. Finally, extensive experiments were carried out to validate the theoretical results.